2019
DOI: 10.1021/acs.accounts.9b00001
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenized Molecular Catalysts: Vibrational Sum-Frequency Spectroscopic, Electrochemical, and Theoretical Investigations

Abstract: Conspectus Rhenium and manganese bipyridyl tricarbonyl complexes have attracted intense interest for their promising applications in photocatalytic and electrocatalytic CO2 reduction in both homogeneous and heterogenized systems. To date, there have been extensive studies on immobilizing Re catalysts on solid surfaces for higher catalytic efficiency, reduced catalyst loading, and convenient product separation. However, in order for the heterogenized molecular catalysts to achieve the combination of the best as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 78 publications
(174 reference statements)
1
46
0
Order By: Relevance
“…(b) A representative VSFG spectra of the nitrile-stretch of 4-mercaptobenzonitrile (4-MBN) on gold as a function of potential, adapted from a publication by Sarkar et al 63 (c) The electrochemical VSFG set-up used in the Lian lab. Figures (a) and (c) are adapted from a publication by Ge et al 64 Stark shift measurements have been successfully reported for a range of catalysts attached to various metal and semiconductor surfaces with suitable anchoring groups. Synthetic efforts have contributed significantly by functionalizing the molecules with anchoring groups that attach to Au electrode surfaces with thiolate, nitrile, or isocyanide groups, or to metal-oxide surfaces with carboxylate, or phosphate anchoring groups.…”
Section: IVmentioning
confidence: 99%
“…(b) A representative VSFG spectra of the nitrile-stretch of 4-mercaptobenzonitrile (4-MBN) on gold as a function of potential, adapted from a publication by Sarkar et al 63 (c) The electrochemical VSFG set-up used in the Lian lab. Figures (a) and (c) are adapted from a publication by Ge et al 64 Stark shift measurements have been successfully reported for a range of catalysts attached to various metal and semiconductor surfaces with suitable anchoring groups. Synthetic efforts have contributed significantly by functionalizing the molecules with anchoring groups that attach to Au electrode surfaces with thiolate, nitrile, or isocyanide groups, or to metal-oxide surfaces with carboxylate, or phosphate anchoring groups.…”
Section: IVmentioning
confidence: 99%
“…Self-assembled monolayers (SAM) of ReS and ReSS on Au films were probed by SFG to characterize the synthesized molecular catalyst as heterogenized on gold surfaces, with an emphasis on characterization of the binding motif of the complexes on the surface. SFG is a surface-selective technique with submonolayer sensitivity (Nihonyanagi et al, 2013;Shen, 2013;Ge et al, 2019). When combined with computational modeling, it can provide information on molecular orientation at the interface.…”
Section: Sum Frequency Generation Spectroscopymentioning
confidence: 99%
“…The orientation and properties of molecular catalysts on electrode surfaces can be analyzed by combining vibrational sum-frequency generation (SFG) spectroscopy and computational modeling (Anfuso et al, 2011(Anfuso et al, , 2012Clark et al, 2016Clark et al, , 2018bGe et al, 2016Ge et al, , 2017. The resulting insights should be particularly informative for the rational design of catalytic materials (Ge et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] In parallel, the increasing interest for in situ and operando microscopic and spectroelectrochemical (SEC) techniques applied to both, the homogeneous and heterogeneous systems has led to a strong improvement in the fundamental understanding of the factors governing the CO 2 RR process. [28][29][30][31][32] In spite of this, further improvement of the catalyst performance in terms of activity, selectivity and stability is highly desired to match the requirements for practical applications.…”
Section: Introductionmentioning
confidence: 99%